2019
DOI: 10.1101/690628
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BR-bodies provide selectively permeable condensates that stimulate mRNA decay and prevent release of decay intermediates

Abstract: AbstractBiomolecular condensates play a key role in organizing RNAs and proteins into membraneless organelles. Bacterial RNP-bodies (BR-bodies) are a biomolecular condensate containing the RNA degradosome mRNA decay machinery, but the biochemical function of such organization remains poorly defined. Here we define the RNA substrates of BR-bodies through enrichment of the bodies followed by RNA-seq. We find that long, poorly translated mRNAs, small RNAs, and antisense RNAs are t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(55 citation statements)
references
References 86 publications
1
53
0
Order By: Relevance
“…For a more in-depth review of BR-body function and phylogenetic distribution, see Muthunayake et al (4). (21) In vitro (18) In vitro (18) In vitro (18) In vitro (22) In vitro (22) In vitro (22) In vitro (47) In vitro (23) In vivo In vitro spherical (23,24,26) In situ icosahedral (95)(96)(97)(98) In situ (25,29) In vitro (23) In vivo (91) In vitro (26) In vitro (23,24,26) ND…”
Section: Current Evidence Demonstrates That Llps May Mediate Subcellumentioning
confidence: 99%
See 3 more Smart Citations
“…For a more in-depth review of BR-body function and phylogenetic distribution, see Muthunayake et al (4). (21) In vitro (18) In vitro (18) In vitro (18) In vitro (22) In vitro (22) In vitro (22) In vitro (47) In vitro (23) In vivo In vitro spherical (23,24,26) In situ icosahedral (95)(96)(97)(98) In situ (25,29) In vitro (23) In vivo (91) In vitro (26) In vitro (23,24,26) ND…”
Section: Current Evidence Demonstrates That Llps May Mediate Subcellumentioning
confidence: 99%
“…In vitro (17,18) In vivo (17) In vivo (31) In vitro (17) proteobacteria; these foci do not form under mRNA depletion (17). Moreover, RNase E CTD foci coalesce into larger spherical structures in Escherichia coli.…”
Section: Current Evidence Demonstrates That Llps May Mediate Subcellumentioning
confidence: 99%
See 2 more Smart Citations
“…We proceeded to characterize the properties of these protein condensates and the dynamics of the encapsulated supercharged GFP. Literature on condensate formation in bacteria remains sparse, but recent reports have shed light on endogenous RNP-bodies (known as BR-bodies) formed in C. crescentus from a protein, RNase E, which contains an unstructured C-terminal domain responsible for intracellular phase separation (6,7). In addition to BRbodies, numerous studies have reported both artificially engineered and common endogenous bacterial compartments (2,11,21,22).…”
Section: Condensed Phase Is Distinct From Inclusion Bodies and Is Dynmentioning
confidence: 99%